Community Satisfaction with Administrative Services and its Impact on the Efficiency of Resource Management in Rumbuk Village - Agus Satriawan; Sab'ul Masani (Saniya Institute, 2025)
The objective of this study is to analyze the impact of community satisfaction on administrative services and its effect on the efficiency of resource management in Rumbuk Village, Sakra District, East Lombok Regency. The study's sample population consists of 30 respondents. The data analysis method employed is simple linear regression, preceded by a thorough examination of the prerequisite assumptions. The regression test results indicate that community satisfaction with administrative services exerts a significant influence on the efficiency of resource management in Rumbuk Village. This assertion is substantiated by a statistical significance value of 0.000 0.05, indicating a positive directional relationship. The public satisfaction variable contributes 94% to the efficiency of resource management, while the remaining 6% is influenced by other factors not observed in this study.